Antiproliferative and cytotoxic activities of furocoumarins of Ducrosia anethifolia - Javad Mottaghipisheh; Márta Nové; Gabriella Spengler; Norbert Kúsz; Judit Hohmann; Dezső Csupor (Taylor & Francis Group, 2018)
Context: Phytochemical and pharmacological data on Ducrosia anethifolia (DC.) Boiss. (Apiaceae), an Iranian medicinal plant, are scarce; however, furocoumarins are characteristic compounds of D. anethifolia. Objective: Our experiments identify the secondary metabolites of D. anethifolia and assess their antitumor and anti-multidrug resistance activities. Materials and methods: Pure compounds were isolated from the extract of aerial parts of the plant by chromatographic methods. Bioactivities were tested on multidrug resistant and sensitive mouse T-lymphoma cell lines. The inhibition of the cancer MDR efflux pump ABCB1 was evaluated by flow cytometry (at 2 and 20 µM). A checkerboard microplate method was applied to study the interactions of furocoumarins and doxorubicin. Toxicity was studied using normal murine NIH/3T3 fibroblasts. Results: Thirteen pure compounds were isolated, nine furocoumarins namely, pabulenol (1), (+)-oxypeucedanin hydrate (2), oxypeucedanin (3), oxypeucedanin methanolate (4), (−)-oxypeucedanin hydrate (5), imperatorin (6), isogospherol (7), heraclenin (8), heraclenol (9), along with vanillic aldehyde (10), harmine (11), 3-hydroxy-α-ionone (12) and 2-C-methyl-erythrytol (13). Oxypeucedanin showed the highest in vitro antiproliferative and cytotoxic activity against parent (IC50  = 25.98 ± 1.27, 40.33 ± 0.63 µM) and multidrug resistant cells (IC50  = 28.89 ± 0.73, 66.68 ± 0.00 µM), respectively, and exhibited slight toxicity on normal murine fibroblasts (IC50  = 57.18 ± 3.91 µM). Discussion and conclusions: Compounds 2, 3, 5, 7, 10-13 were identified for the first time from the Ducrosia genus. Here, we report a comprehensive in vitro assessment of the antitumor activities of D. anethifolia furocoumarins. Oxypeucedanin is a promising compound for further investigations for its anticancer effects.